Mapping and Validation of Peptides Differentially Recognized by Antibodies from the Serum of Yellow Fever Virus-Infected or 17DD-Vaccinated Patients - Eneida Santos Oliveira; Naiara Clemente Tavares; Stella Garcia Colombarolli; Izabella Cristina Andrade Batista; Camila Sales Nascimento; Philip Louis Felgner; Rafael Ramiro de Assis; Carlos Eduardo Calzavara-Silva (Viruses, 2022)
Yellow Fever disease is caused by the Yellow Fever virus (YFV), an arbovirus from the Flaviviridae family. The re-emergence of Yellow Fever (YF) was facilitated by the increasing urbanization of sylvatic areas, the wide distribution of the mosquito vector, and the low percentage of people immunized in the Americas, which caused severe outbreaks in recent years, with a high mortality rate. Therefore, serological approaches capable of discerning antibodies generated from the wild-type (YFV-WT) strain between the vaccinal strain (YFV-17DD) could facilitate vaccine coverage surveillance, enabling the development of strategies to avoid new outbreaks. In this study, peptides were designed and subjected to microarray procedures with sera collected from individuals infected by WT-YFV and 17DD–YFV of YFV during the Brazilian outbreak of YFV in 2017/2018. From 222 screened peptides, around ten could potentially integrate serological approaches aiming to differentiate vaccinated individuals from naturally infected individuals. Among those peptides, one was synthesized and validated through ELISA.